MiRNA and associated inflammatory changes from baseline to hypoglycemia in type 2 diabetes - Ramanjaneya, Manjunath; Priyanka, Ruth; Bensila, Milin; Jerobin, Jayakumar; Pawar, Krunal; Sathyapalan, Thozhukat; Abou-Samra, Abdul Badi; Halabi, Najeeb M.; Moin, Abu Saleh Md; Atkin, Stephen L.; Butler, Alexandra E. (Frontiers in Endocrinology, 2022)
Objective Hypoglycemia in type 2 diabetes (T2D) increases morbidity and mortality but the underlying physiological response is still not fully understood, though physiological changes are still apparent 24 hours after the event. Small noncoding microRNA (miRNA) have multiple downstream biological effects that may respond rapidly to stress. We hypothesized that hypoglycemia would induce rapid miRNA changes; therefore, this pilot exploratory study was undertaken. Methods A pilot prospective, parallel study in T2D (n=23) and controls (n=23). Insulin-induced hypoglycemia (2mmol/l: 36mg/dl) was induced and blood sampling performed at baseline and hypoglycemia. Initial profiling of miRNA was undertaken on pooled samples identified 96 miRNA that were differentially regulated, followed by validation on a custom designed 112 miRNA panel. Results Nine miRNAs differed from baseline to hypoglycemia in control subjects; eight were upregulated: miR-1303, miR-let-7e-5p, miR-1267, miR-30a-5p, miR-571, miR-661, miR-770-5p, miR-892b and one was downregulated: miR-652-3p. None of the miRNAs differed from baseline in T2D subjects. Conclusion A rapid miRNA response reflecting protective pathways was seen in control subjects that appeared to be lost in T2D, suggesting that mitigating responses to hypoglycemia with blunting of the counter-regulatory response in T2D occurs even in patients with short duration of disease. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT03102801?term=NCT03102801&draw=2&rank=1, identifier NCT03102801.